Proteomic profiling reveals sub proteomes of the human placenta. (November 2017) - Heywood, Wendy E.; Preece, Rhian-Lauren; Pryce, Jeremy; Hallqvist, Jenny; Clayton, Robert; Virasami, Alex; Mills, Kevin; Sebire, Neil J.
Abstract: Proteomic characterisation of the placenta has largely been focused on effect of disease, anatomical features or specific cell types. We describe an unbiased proteomic mapping analysis to investigate how the placental proteome changes throughout the organ. A transverse slice of a human placenta was sectioned into 1 × 1cm samples. Sections were analysed using label free proteomics. Analysis revealed two distinct sub-proteomes that did not have anatomical significance. One had a muscular proteome and the other had distinct immunomodulation functions. Chorionic plate enriched proteins highlighted the fetal tissues high energy requirements whilst mechanisms of the decidua observed included modulation of cortisone levels. Graphical abstract: Highlights: The placenta proteome in not uniform across the organ. Antigen presentation appears to represent a significant sub-proteome. The fetal side proteome is enriched for processes related to high energy demand. Mechanical sheer stress response is a process enriched at the maternal side. Findings have implications for future placenta proteomics sampling protocols.